Formação de cidadãos e a educação em ciências com enfoque CTS: uma releitura à luz da teoria atorrede - Kristianne Lina Figueiredo (2018)
In the scope of research in Science Education, the recognized slogans Scientific and Technological Literacy (STL) and Science, Technology and Society (STS), which have opened the way for the debates about the formation of citizens, have converged towards what is meant by a STS in a extended version. However, the jargon of an education for citizenship has permeated official documents throughout the world for several decades, without achieving satisfactorily the desired success. Therefore, our proposal is to carry out a re-reading of STS education in the light of the Actor-Network Theory (ANT), intending to configure new guidelines for it. This re-reading is carried out in two stages: in the first, we proceed to what we call the 'unfreezing' of contemporary frames of society, S&T and politics, culminating in the respective alternative notions that emerge from ANT; in the second, we review the relationship between citizens' formation and STS education in an extended version, through the reflections raised by the previous stage on the concept of citizen. In the development of the first stage: (i) understanding the 'social' as the movement of associations, the current version of society was dissolved, giving rise to the idea of hybrid (re) groupings (human and nonhuman) whose major project is of collecting the collective; (ii) by making explicit the science and technology in action, we detail the process of fabrication of facts and artifacts, evidencing the connections chaining between 'subjects' and 'objects'; (iii) these two tasks fulfilled, the asymmetries of society and nature, subject and object, inherited from the Modernity project, are replaced by the recognition of human and non-human agency and a dynamic flow of connections between them; and (iv) in order to contemplate this hybrid reality and provisional configurations, politics is problematized in terms of the issue of representation, being conceived as the task of making the new associations into a viable set, that is, of leading to the composition of collectives and, later, to delineate a common world. In the second stage, we redefine the notion of citizen, becoming understood by the real citizen as one who performs in practice, that is, an actor who, in performing his performance, approaches the projection of the body politic under the same denomination (ideal citizen) . As a result, the formation of citizens also assumes another meaning, and is now understood as the practice of intentionally influencing the connections established by the actors, in order to favor performances that approach the idealized projection. Thus, the acronym STS itself becomes questionable, because there is no preconceived society, nor different spheres that are interrelated. In this sense, we propose to replace the slogan education with a STS approach, by education for awareness raising (EAR). Finally, by establishing a dialogue between the results of previous discussions and reflections and the revised literature, we outline some guidelines for Science Education.